A new crinoid fauna from the Taiyuan Formation (early Permian) of Henan, North China. (9th May 2018) - Mao, Yingyan; Webster, Gary D.; Ausich, William I.; Li, Yue; Wang, Qiulai; Reich, Mike
Abstract: A diverse Permian crinoid fauna is reported from the Taiyuan Formation, Dajian Member (Asselian) at Anyang, northeastern Henan Province of the North China Craton. The specimens are well preserved, including articulated crowns and cups. The fauna contains representatives of each of the major Paleozoic crinoid clades: Cladida (including the Flexibilia), Disparida, and Camerata. Identified genera suggest a greater affinity with North American faunas than with Tethyan faunas. Four new species, Neoprotencrinus anyangensis, Ulocrinus qiaoi, Artichthyocrinus limani, and Synbathocrinus chenae, are proposed herein. UUID:http://zoobank.org/D08DDDCD-485C-45CC-A014-C1CB58C26588